THE USE OF DISTRIBUTED CONTROL SYSTEMS IN THE OPERATION OF ESSENTUKI MINERAL WATER FIELD - M. M. Mardoyan; G. L. Bondareva; E. S. Levitsky (Современная наука и инновации, 2022)
The article describes the Essentuki Deposit, given the existing problems in the operation of wells, indicated the need for mathematical modeling in the determination of rational modes of production wells.